The hypoglossal canal and the origin of human vocal behavior - Kay, Richard F. (The National Academy of Sciences, 1998)
The mammalian hypoglossal canal transmits the nerve that supplies the muscles of the tongue. This canal is absolutely and relatively larger in modern humans than it is in the African apes (Pan and Gorilla). We hypothesize that the human tongue is supplied more richly with motor nerves than are those of living apes and propose that canal size in fossil hominids may provide an indication about the motor coordination of the tongue and reflect the evolution of speech and language. Canals of gracile Australopithecus, and possibly Homo habilis, fall within the range of extant Pan and are significantly smaller than those of modern Homo. The canals of Neanderthals and an early “modern” Homo sapiens (Skhul 5), as well as of African and European middle Pleistocene Homo (Kabwe and Swanscombe), fall within the range of extant Homo and are significantly larger than those of Pan troglodytes. These anatomical findings suggest that the vocal capabilities of Neanderthals were the same as those of humans today. Furthermore, the vocal abilities of Australopithecus were not advanced significantly over those of chimpanzees whereas those of Homo may have been essentially modern by at least 400,000 years ago. Thus, human vocal abilities may have appeared much earlier in time than the first archaeological evidence for symbolic behavior.